1988
DOI: 10.1111/j.1399-302x.1988.tb00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Saliva increases serum IgG retention on Streptococcus mutans

Abstract: The purpose of this investigation was to determine if saliva would affect the retention of serum antibodies to S. mutans. A quantitative enzyme‐linked immunosorbent assay (ELISA) was used to estimate total IgM, IgG and IgA after applications of whole saliva and absorbed serum to equal but separate aliquots of S. mutans. Total antibodies were also estimated after the sequential application of saliva and adsorbed serum to the same aliquot of S. mutans. Significantly more IgG, but not IgM or IgA, was retained on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Rather, these experiments indicate that activation above and suppression below control levels are transient processes that eventually lead to modulation of antibody levels around nonimmune levels in conventional rats, even though antigenic stimulation persists. This suggests that the reason humans do not differ in tertns of antibody to S. mutans, despite great differenees in caries experience (15,(21)(22)(23), is that chronic infection has produeed a stable immunologic balance that prevents further responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, these experiments indicate that activation above and suppression below control levels are transient processes that eventually lead to modulation of antibody levels around nonimmune levels in conventional rats, even though antigenic stimulation persists. This suggests that the reason humans do not differ in tertns of antibody to S. mutans, despite great differenees in caries experience (15,(21)(22)(23), is that chronic infection has produeed a stable immunologic balance that prevents further responses.…”
Section: Discussionmentioning
confidence: 99%
“…People with dental caries have more S. mutans in saliva and dental plaque than do people without caries (9,11,27), suggesting that the ability to resist infection may be associated with natural resistance to dental caries. However, people who differ regarding caries experienee tend to have similar levels of antibodies to S. mutans (15,(21)(22)(23). The lack of conclusive evidence for protective immunity contributes to skepticism concerning the role immunity plays in natural resistance to dental caries (24).…”
mentioning
confidence: 99%
“…There is increasing evidence for a structure/function (specificity) relationship of the TcR, in that only a very limited number of TcR a/p combinations is able to recognize a given MHC-antigen complex . ' The goal of this study was to analyze the specific R R structures expressed by CTL triggered during an infection of the mouse with the natural pathogen LCMV LCMV is a member of the arenavirus family (for review see [14]). The Correspondence: Hans Hengartner, Department of Experimental Pathology, University Hospital, CH-8091 Zurich, Switzerland Abbreviations: aa: Amino acid NP: Nucleoprotein GP: Glycoprotein SC: Spleen cell VV: Vaccinia virus shorter RNA molecule of its bisegmented genome encodes a 63-kDa nucleoprotein (NP) and a precursor glycoprotein (GP), which is cleaved into a 44-kDa GP1 and a 35-kDa GP2 [15, 161. With the help of recombinant vaccinia virus (rVV), both the NP as well as the GP have been shown to elicit specific CTL in H-2b mice [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…If, as the current investigation suggests, suppression of protective salivary antibodies follows natural infections with cariogenic bacteria, then one might expect to find that humans who have mutans streptococci in their mouths for long periods of time would have low levels of antibodies, and that these levels would be similar to those found in humans with little or no detectable mutans streptococci. Although this hypothesis is not uniformly supported by the existing literature (3), some studies have found that human subjects who differ by caries experience do have similar levels of antibody to cariogenic bacteria (6,8,9). The phenomenon of acquired suppression could affect future prevention strategies.…”
Section: Discussionmentioning
confidence: 96%